The Hybrid Strategy of Thermoactinospora rubra YIM 77501T for Utilizing Cellulose as a Carbon Source at Different Temperatures - Yin, Yi-Rui; Meng, Zhao-Hui; Hu, Qing-Wen; Jiang, Zhao; Xian, Wen-Dong; Li, Lin-Hua; Hu, Wei; Zhang, Feng; Zhou, En-Min; Zhi, Xiao-Yang; Li, Wen-Jun (Frontiers in Microbiology, 2017)
Thermoactinospora rubra YIM 77501T is an aerobic, Gram-positive, spore-forming and cellulose degrading thermophilic actinomycete isolated from a sandy soil sample of a volcano. Its growth temperature range is 28–60°C. The genomic sequence of this strain revealed that there are 27 cellulase genes belonging to six glycoside hydrolase families. To understand the strategy that this strain uses to utilize carbon sources such as cellulose at different temperatures, comparative transcriptomics analysis of T. rubra YIM 77501T was performed by growing it with cellulose (CMC) and without cellulose (replaced with glucose) at 30, 40, and 50°C, respectively. Transcriptomic analyses showed four cellulase genes (TrBG2, TrBG3, TrBG4, and ThrCel6B) were up-regulated at 30, 40, and 50°C. The rate of gene expression of TrBG2, TrBG3, TrBG4, and ThrCel6B were 50°C > 30°C > 40°C. One cellulase gene (TrBG1) and two cellulase genes (TrBG5 and ThrCel6A) were up-regulated only at 30 and 50°C, respectively. These up-regulated cellulase genes were cloned and expressed in Escherichia coli. The enzymatic properties of up-regulated cellulases showed a variety of responses to temperature. Special up-regulated cellulases TrBG1 and ThrCel6A displayed temperature acclimation for each growth condition. These expression patterns revealed that a hybrid strategy was used by T. rubra to utilize carbon sources at different temperatures. This study provides genomic, transcriptomics, and experimental data useful for understanding how microorganisms respond to environmental changes and their application in enhancing cellulose hydrolysis for animal feed and bioenergy production.